LEVEL OF SPINAL INVOLVEMENT IN PATIENTS OPERATED FOR SPINAL TUBERCULOSIS - Ali, Mumtaz; Khan, Hayat Muhammad; Khanzada, Khalid; Usman, Muhammad; Hussain, Ramzan; Rehman, Zia ur (Journal of Postgraduate Medical Institute, 2012)
Objective: To determine the frequency of different levels of spinal involvement in patients operated for spinal tuberculosis. Methodology: This observational study was conducted in the Department of Neurosurgery Lady Reading Hospital Peshawar from January 2008 to December 2010. In this study medical record of all patients operated for spinal tuberculosis were analyzed. The frequency of different spinal levels involved was determined. Patients were divided into five groups based on the involvement of different vertebral level i.e. cervical, upper dorsal, lower dorsal lumbar and sacral. Data stratified regarding age, sex and locality. Results were analyzed and presented in the form of tables, bar and pie charts by using SPSS software version 11 for analysis. Results: A total of 81 patients with spinal tuberculosis were operated during this period. Their age ranged from 13 to 65 years. Patients presented with male to female ratio of 1.25 to 1. Per-operatively majority of the patients (i.e., 49.38%) had involvement of lower dorsal spine (D7 to D12), while 19.75% had involved cervical vertebrae, 22.22% involved upper dorsal spine that is from D1 to D6 while only 8% had lumbar vertebrae involved. Most of the patients had multilevel involvement, which is 70.37%. Conclusion: This study shows that most of the patients with spinal tuberculosis involve lower dorsal spine while lumbar area in very little and no sacral area involvement. We found that most of the time it was multiple level involvement rather than single vertebrae.